Spinoza and Hobbes: Notes for a comparative study of their respective political philosophies - Salas Muñoz, Mario (2025)
In this paper, the author analyzes the differences between the philosophical political doctrines exposed in Thomas Hobbes’ Leviathan and Baruch Spinoza’s Theological Political Treatise. He concludes the differences are based upon the ways in which each author conceive Natural Right and the obligation to respect covenants.